(untitled) (Eurasian Medical Research Periodical, 2026)
Early perinatal screening is important for the timely detection of congenital malformations and improving maternal and child health. The purpose of this study is to conduct a comparative analysis of the effectiveness, coverage and systemic problems of the early perinatal screening system in Central Asian countries. The study analyzed secondary data based on data from international organizations, national health reports and scientific literature. Comparative analysis, statistical evaluation and a systematic approach were used as research methodologies. Screening coverage, the level of use of diagnostic technologies, the availability of qualified specialists, and the introduction of modern methods, including non-invasive prenatal testing (NIPT), were studied. The results showed that there are significant differences in the coverage and effectiveness of the perinatal screening system among the Central Asian countries. While some countries are experiencing positive changes as a result of reforms and technological innovations in the health system, in other regions limited financial resources, insufficiently developed medical infrastructure, and low awareness of the population were identified as the main problems. It was also noted that the level of integration of digital technologies and artificial intelligence into prenatal diagnostics varies across regions. Improving the early perinatal screening system in Central Asian countries requires an integrated approach. In this process, standardization of health policies, development of medical infrastructure, increasing human resources capacity, and raising awareness of the population are important.